Penggunaan Media ICT dalam Pembelajaran - Fajar Ramadan; Najwa Nur Fajriah; Suhartini Suhartini; Usep Setiawan (JURNAL EDUKASI NONFORMAL, 2022)
There are many important roles in the world of education, one of which is included in an important role in the world of education, namely information and communication technology (ICT). If in Indonesia ICT is better known as ICT (information and communication technology). The existence of ICT or ICT in the world of education is for a teacher to have the ability to compile, integrate and apply this ICT or ICT-based learning. The purpose of this ICT-based learning is to make the teaching and learning process more interesting and fun, so that students will be excited when the teaching and learning process. Currently, every teacher should have an awareness of the importance of understanding and mastering technology. Because the competence that must be possessed by a reliable and professional teacher is that the teacher must be able to master ICT. The benefit of the mastery and application of ICT is to improve the quality of Indonesia's national education. The use of e-mail, e-book, e-library, etc., is the support of technology in the world of education. ICT has had an impact on the world of education, especially in the learning process. Therefore, a teacher must be able to combine the use of technology with effective and strategic instruction.